Evidence of an age gradient along the line of sight in the nuclear stellar disc of the Milky Way - Nogueras Lara, Francisco; Schultheis, M.; Najarro, F.; Sormani, Mattia C.; Gadotti, D. A.; Rich, R. M. (Astronomy and astrophysics, 2023)
The nuclear stellar disc (NSD) is a flat dense stellar structure at the heart of the Milky Way. Recent work has shown that analogous structures are common in the nuclei of external spiral galaxies, where there is evidence of an age gradient that indicates that they form inside-out. However, the characterisation of the age of the NSD stellar population along the line of sight is still missing due to its extreme source crowding and the high interstellar extinction towards the Galactic centre. We aim to characterise the age of the stellar population at different average Galactocentric NSD radii to investigate for the first time the presence of an age gradient along the line of sight.
Online veröffentlicht am 10. März 2023
Gesehen am 12.12.2023